Antimicrobial, Conductive, and Mechanical Properties of AgCB/PBS Composite System - Chatchai Veranitisagul; Worawat Wattanathana; Suttipong Wannapaiboon; Yuranan Hanlumyuang; Kankavee Sukthavorn; Nollapan Nootsuwan; Siwaruk Chotiwan; Witchukorn Phuthong; Suchada Jongrungruangchok; Apirat Laobuthee (Journal of Chemistry)
Demand for environmentally friendly plastic materials which are obtained from renewable resources such as biomass-based polyesters is of concern. Herein, the enhanced characteristic performances of poly(butylene succinate) (PBS) by employing the fabrication of PBS-based composites with the nanosilver-coated carbon black (AgCB) using an injection-molding method are reported. The preformed AgCB additives are priorly prepared by the benzoxazine oxidation method. Phase characterization of the obtained composite materials examined by X-ray diffraction (XRD) reveals the crystalline PBS matrix and the presence of metallic silver particles, confirming the successful fabrication of the composite materials. Detailed analyses on thermal, mechanical, electrical, and antimicrobial properties of the composite materials are reported. The AgCB-PBS composite materials provide such potential features by an enhancement of electrical conductivity and the antimicrobial activity by an inhibition against E. coli and C. albicans. These AgCB-PBS composite materials show the possibility to be an option for antielectrostatic and antimicrobial applications such as for the production of smart, environmentally friendly keyboards.